ENZYME KINETICS OF PROTEASE FROM HYPSIZYGUS ULMARIUS - SHIVASHANKAR M; PREMKUMARI B (International Journal of Pharma and Bio Sciences, 2014)
Enzyme kinetics of protease activity from extract of edible mushroom, Hypsizygus ulmarius were carried out. The optimum PH and temperature for protease activity were found to be at 10 and 40oC respectively. The PH and temperature stability profile shows that protease enzyme is stable under alkaline conditions and up to 50oC. The extract had the greatest activity in 1% of casein as a substrate with Km and Vmax of 0.25mM and 0.45mM respectively. The effect of metals on activity of protease was greatly enhanced with NaCl and NiSO4, However, 100% activity was seen with addition of FeSO4, and decreased with ZnSO4. Drastic inhibition of protease activity was seen in PMSF at 10mM.